Apoptotic induction by pinobanksin and some of its ester derivatives from Sonoran propolis in a B-cell lymphoma cell line. (5th December 2015) - Alday, Efrain; Valencia, Dora; Carreño, Ana Laura; Picerno, Patrizia; Piccinelli, Anna Lisa; Rastrelli, Luca; Robles-Zepeda, Ramon; Hernandez, Javier; Velazquez, Carlos
Abstract: Propolis is a resinous substance produced by honeybees ( Apis mellifera ) from the selective collection of exudates and bud secretions from several plants. In previous works, we reported the antiproliferative activity of Sonoran propolis (SP) on cancer cells; in addition we suggested the induction of apoptosis after treatment with SP due to the presence of morphological changes and a characteristic DNA fragmentation pattern. Herein, in this study we demonstrated that the antiproliferative effect of SP is induced through apoptosis in a B-cell lymphoma cancer cell line, M12.C3.F6, by an annexin V-FITC/Propidium iodide double labeling. This apoptotic effect of SP resulted to be mediated by modulations in the loss of mitochondrial membrane potential (ΔΨm ) and through activation of caspases signaling pathway (3, 8 and 9). Afterward, in order to characterize the chemical constituents of SP that induce apoptosis in cancer cells, an HPLC-PDA-ESI-MS/MS method followed by a preparative isolation procedure and NMR spectroscopy analysis have been used. Eighteen flavonoids, commonly described in propolis from temperate regions, were characterized. Chrysin, pinocembrin, pinobanksin and its ester derivatives are the main constituents of SP and some of them have never been reported in SP. In addition, two esters of pinobanksin (8 and13 ) are described by first time in propolis samples in general. The antiproliferative activity on M12.C3.F6 cells through apoptosis induction was exhibited by pinobanksin (4 ), pinobanksin-3- O -propanoate (14 ), pinobanksin-3- O -butyrate (16 ), pinobanksin-3- O -pentanoate (17 ), and the already reported galangin (11 ), chrysin (9 ) and CAPE. To our knowledge this is the first report of bioactivity of pinobanksin and some of its ester derivatives as apoptosis inducers. Further studies are needed to advance in the understanding of the molecular basis of apoptosis induction by SP and its constituents, as well as the structure–activity relationship of them. Graphical abstract: Highlights: Antiproliferative effect of SP on M12.C3.F6 cells is through apoptosis induction. Apoptosis induced by SP is mediated by modulations on ΔΨm and caspases activation. Chemical composition of SP was analyzed by HPLC-PDA-ESI/MS/MS and NMR. Eighteen flavonoids described in propolis from temperate regions were characterized. Pinobanksin and some its derivatives from SP were apoptotic inducer compounds.